Enhancing Biotechnology Education through BioVate Competition: Increasing Conceptual Understanding and Science Communication in Science Education - Kurniasih, Septi (PendIPA Journal of Science Education, 2025)
The goal of this study was to explore the effectiveness of implementing competition during a learning process to elevate motivation and science communication skills in a particular biotechnology education course among the third-year science education students at Universitas Sultan Ageng Tirtayasa using the BioVate competition, in which incorporates project-based learning (PjBL) within competitions during learning process. It is a unique model for competitive learning. A quasi-experimental model was employed on a sample comprising 67 undergraduate students. Students had no prior biotechnology training and the intervention lasted four weeks. It comprised problem identification and solving, solution development, as well as a culmination competition. In the assessment, significant changes with respect to motivation (mean 2.7 to 4.1, d 0.54) and comprehension (mean 8.7 to 18 out of 20, d 0.92) were noted in pretest-posttest analysis. In the observation, interview and document analysis, participants noted improvement with respect to good communication, articulation of complex ideas, increased self-confidence, and effective use of visual aids. The major premise of the BioVate model, the ability to tackle real problems (for example, the use of CRISPR technology for developing pest-resistant crops), was reported to have fostered intrinsic motivation and closed the theoretical-practical gap. These findings also support constructivist learning theory and self-determination theory by highlighting the impact of competition and collaboration on engagement. This new approach contributes to increasing comprehensive conceptual understanding in biotechnology and builds skills in future educators and science communicators to address societal issues with an interdisciplinary approach.